Task-based approach importance for the occupational risk assessment: the ease of particles exposure in feed industry - Viegas, Susana (2017)
Introduction: Task-based exposure assessment approach recognizes that only through a more detailed and comprehensive understanding of tasks can control measures be correctly designed to reduce exposure. Working in the feed industry involves risks of exposure to grain dust and its microbial contents; possible leading to pathological symptoms and functional changes of the airways. Objective: The main goal of this research work was to demonstrate the importance and utility of task-based exposure assessment in occupational risk assessment and in the following exposure control interventions. Methodology: Exposure assessment was done by task using two different exposure metrics: particle mass concentration measured in 5 different sizes and particle number concentration based on results given in six different diameters sizes. The measurements were done with a direct-reading instrument and all the measurements were conducted continuously with the duration of 5 minutes near the worker's nose and during each task performance.